2019
DOI: 10.1177/0886260519842170
|View full text |Cite
|
Sign up to set email alerts
|

Parental Warmth and Interpersonal Empathy as Predictors of Sexual Assault Bystander Intervention Efficacy

Abstract: Sexual victimization rates of women in the United States remain worryingly high. Much research has focused on the reduction of sexual violence with varying levels of success. One promising avenue of sexual violence reduction research provides evidence that bystanders who intervene appropriately can effectively contribute to a reduction in sexual assault. The Ecological Model for Bystander Intervention provides a conceptual framework for investigating what motivates and what inhibits bystanders. Empirical evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…These findings combined with those of Kotze and Turner (2019) demonstrate the complex relation of parenting to empathic concern and bystander intervention. Kotze and Turner documented that perceived parental warmth was related to higher levels of empathic concern which was related to greater bystander intervention efficacy in cases of sexual assault.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…These findings combined with those of Kotze and Turner (2019) demonstrate the complex relation of parenting to empathic concern and bystander intervention. Kotze and Turner documented that perceived parental warmth was related to higher levels of empathic concern which was related to greater bystander intervention efficacy in cases of sexual assault.…”
Section: Discussionmentioning
confidence: 66%
“…Also, evidence suggests that parents who engage in warm parenting practices report higher levels of empathy (Stern et al, 2015). A number of empirical studies establish that perceived parental warmth is related to children’s self-reported levels of empathy (Kotze & Turner, 2019; Wright et al, 2017; Zhou et al, 2002). Kotze and Turner (2019) found that parental warmth was positively related to bystander intervention through the mediating variable of empathy among college students.…”
Section: Introductionmentioning
confidence: 99%
“…While the majority of bystander intervention research involving college students has focused on the prevention of sexual assault, there is a similar pattern of findings with respect to predictors of bystander intervention. For example, Kotze and Turner (2021) studied sexual harassment-related upstanding behavior in a sample of college students and found that empathy served as a mediator between reports of parental warmth and bystander self-efficacy. In a related study of male college students’ bystander behaviors when witnessing sexually aggressive behavior in men, Murphy Austin et al (2016) found that both men’s individual attitudes and behaviors and their perception of their peer’s attitudes and behaviors predict intentions to take part in bystander intervention behaviors, as well as actual behaviors.…”
Section: Bystander Research In College Studentsmentioning
confidence: 99%
“…The vast majority of studies examining the relationship between bystander interventions and bullying reduction have involved younger populations and may not be directly applicable to college settings. Comparable studies on preventing bullying in college students are rarer, but they often examine bystander responses in reducing sexual harassment and violence (Kotze & Turner, 2021; McMahon et al, 2013; Murphy Austin et al, 2016). Thus, the purpose of the current study was to examine the predictors of upstanding behavior in college-aged students in the context of culturally-motivated bullying incidents with an eye toward understanding: (a) how hypothetical witnesses would perceive different types of culturally-motivated incidents, (b) what would predict upstanding behavioral intentions, and (c) to what extent witness or victim characteristics, such as a history of being victimized, might influence witness responses.…”
mentioning
confidence: 99%